2005
DOI: 10.1227/01.neu.0000154132.40212.6e
|View full text |Cite
|
Sign up to set email alerts
|

Simple Decompression or Anterior Subcutaneous Transposition for Ulnar Neuropathy at the Elbow: A Cost-minimization Analysis—Part 2

Abstract: Although clinically equally effective, simple decompression was associated with lower cost than anterior subcutaneous transposition for the treatment of ulnar neuropathy at the elbow. Compared with anterior subcutaneous transposition, we recommend simple decompression for the treatment of idiopathic ulnar neuropathy at the elbow.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
28
0
5

Year Published

2007
2007
2017
2017

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 58 publications
(33 citation statements)
references
References 3 publications
0
28
0
5
Order By: Relevance
“…20 Overall, simple decompression was found to have the highest utility, and a cost analysis study also found it to be less expensive than subcutaneous transposition. 16 …”
Section: Analysis Of Results By Outcomes Measurementioning
confidence: 99%
“…20 Overall, simple decompression was found to have the highest utility, and a cost analysis study also found it to be less expensive than subcutaneous transposition. 16 …”
Section: Analysis Of Results By Outcomes Measurementioning
confidence: 99%
“…Interestingly, most randomized trials ultimately recommend simple decompression as the procedure of choice based either on technical simplicity [22] or lower complication rates and procedural cost [1]. The metaanalysis developed by Zlowodzki et al studied simple decompression versus all forms of transposition and found no statistical difference in outcome.…”
Section: Resultsmentioning
confidence: 99%
“…Advantages of in situ decompression are smaller surgical incisions, less risk of medial antebrachial cutaneous nerve damage [100], no UN devascularisation [97], shorter operating time [101], smaller costs [99] and a faster recovery [102]. Transpositions need more surgical time, are more expensive and have more complications than in situ decompression [99], but can be used in the case of failure [102,103]. It is imperative to avoid damaging the medial antebrachial cutaneous nerve or its branches regardless of the technique, as injury will induce post-operative neuropathic pain in the elbow area [104][105][106].…”
Section: Ulnar Nerve Compression At the Elbowmentioning
confidence: 99%